1998
DOI: 10.1046/j.1432-1327.1998.2581059.x
|View full text |Cite
|
Sign up to set email alerts
|

The StrQ protein encoded in the gene cluster for 5′‐hydroxystreptomycin of Streptomyces glaucescens GLA.0 is a α‐ D‐glucose‐1‐phosphate cytidylyltransferase (CDP‐ D‐glucose synthase)

Abstract: The gene strQ was identified as the last gene of a putative transcription unit, strB1FGHPQ, located in the gene cluster for the production of 5′-hydroxy-streptomycin (OH-Sm) in Streptomyces glaucescens GLA.0. [In contrast, the corresponding operon in the str/sts-gene cluster of the Sm-producer Streptomyces griseus, strB1FGHIK, differs in the two distal genes; Mansouri, K. & Piepersberg, W. (1991) Mol. Gen. Genet. 228, 459Ϫ469.] The deduced StrQ protein exhibited similarities to members of the enzyme family o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…4a. The backbone amide nitrogen of Gly 10 , the carbonyl oxygen of Ser 106 , and the guanidinium group of Arg 111 all lie within hydrogen bonding distance to the carbonyl oxygen, the amino group, and the ring nitrogen, respectively, of the cytosine base. The 2-hydroxyl group of the nucleotide ribose sits within ϳ2.9 Å of the backbone amide nitrogen of Gly 11 and a water molecule, whereas the 3-hydroxyl group lies within 2.9 and 2.7 Å of the backbone nitrogen of Gly 130 and the carbonyl oxygen of Leu 8 , respectively.…”
Section: Table III Kinetic Parameters For the Forward Reactionmentioning
confidence: 94%
“…4a. The backbone amide nitrogen of Gly 10 , the carbonyl oxygen of Ser 106 , and the guanidinium group of Arg 111 all lie within hydrogen bonding distance to the carbonyl oxygen, the amino group, and the ring nitrogen, respectively, of the cytosine base. The 2-hydroxyl group of the nucleotide ribose sits within ϳ2.9 Å of the backbone amide nitrogen of Gly 11 and a water molecule, whereas the 3-hydroxyl group lies within 2.9 and 2.7 Å of the backbone nitrogen of Gly 130 and the carbonyl oxygen of Leu 8 , respectively.…”
Section: Table III Kinetic Parameters For the Forward Reactionmentioning
confidence: 94%
“…[131,132] Interestingly, a DdhA homologue (StrQ) was found in the streptomycin (124) gene cluster of Streptomyces glaucescens, and its cytidylyltransferase activity was verified in vitro. [133] However, TDP-glucose has been implicated as the precursor of the streptose moiety (26) of streptomycin (see also Scheme 4). [122] Thus, StrQ may participate in the biosynthesis of the Nmethyl-l-glucosamine (125) moiety of streptomycin.…”
Section: Cdp-sugarsmentioning
confidence: 99%
“…Deuterium exchange studies have shown that epimerization at C-5 is much more facile than at C-3 and thus likely occurs first. After C-5 epimerization, a ring-flipped intermediate (133) in the 1 C 4 conformation typical of l-sugars is proposed to form in order to avoid steric clashes between the 5-methyl group, the O-1 atom, and His65. Intermediate 133 is likely in equilibrium with a twist-boat conformation (134) in which the C-3 hydrogen atom is orthogonal to the plane of the 4-keto group to facilitate C-3 proton abstraction.…”
Section: Epimerization/isomerizationmentioning
confidence: 99%
“…14 However, only a few biosynthetic genes were heterologously expressed and investigated to characterize the function to date. [15][16][17][18] Among those, the characterization of L-glutamine: syllo-inosamine aminotransferase StsC gave important information to elucidate the aminocyclitol-containing aminoglycosides biosynthetic pathway. 15 Using the hybridization method, Piepersberg and co-workers 15 showed that its homologous gene is conserved in the aminocyclitol antibiotic-producing microorganisms.…”
Section: Introductionmentioning
confidence: 99%